Semen Parameters of Fertile Guinea Pigs (Cavia porcellus) Collected by Transrectal Electroejaculation - Fernando Benavides; Peter Sutovsky; Verónica López; Chelsey Kennedy; Luisa Echevarría (Animals, 2020)
The guinea pig, as a livestock species, is still developing and growing throughout Peru and neighboring countries, as reflected by its increasing export since 2000. However, the selection of proven fertile males is tedious due to the absence of seminal parameter standards and the lack of safe semen collection techniques. Thus, pregnancy detection or live births are required for males’ selection. The purpose of this study was to describe the qualitative and quantitative semen parameters of fertile guinea pig males, to set reference values, and to validate a novel electroejaculation technique for the species. Semen was collected at weekly intervals from sixteen fertile males. Four transrectal electroejaculations were performed per male with 95% successful collections, yielding 39 viable semen samples. Seminal characteristics were as follows: pH 7.0 ± 0.13; ejaculate volume 0.67 ± 0.55 mL; sperm motility 90.81 ± 6.64%; sperm concentration 36.7 ± 28.41 × 106 sperm/mL; sperm count 20.09 ± 17.56 × 106 sperm/ejaculate; percentage of abnormal morphology 18.26 ± 8.52%; and percentage ubiquitinated spermatozoa 5.57 ± 6.28%. These values will serve as a reference to detect best breeding and infertile males rapidly. The described techniques are reproducible by commercial producers.